Utilization of Peroxide Bleached Sugar Palm (Arenga pinnata) Fibre Waste into Cellulose Nano Crystal - Dwi Joko Prasetyo; Nur Evita Fitriana; Wahyu Anggo Rizal; Hernawan; Tri Hadi Jatmiko; Diah Pratiwi; Anggita Sari Praharasti; Roni Maryana; Muslih Anwar; Ria Suryani; Andri Suwanto; Satriyo Krido Wahono; Crescentiana Dewi Poeloengasih (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2022)
Sugar palm (Arenga pinnata) fibre (SPF) waste is a side product of sugar palm starch production and needs to be processed to avoid environmental pollution. Since the SPF has high cellulose content, it can be beneficial if it is valorized into high-value products such as cellulose nanocrystal (CNC). The CNC production from SPF was initiated by cellulose production by using an environmentally friendly peroxide bleaching as elementary chlorine free bleaching method. The CNC production was conducted via sulfuric acid hydrolysis at a temperature of 40°C, solid/liquid ratio of 1:10, and hydrolysis time of 45, 60, 75, and 90 minutes. The same functional groups were observed in all CNC samples, including the appearance of the ester sulfate group. The decrease in yield and crystallinity index (CrI) as the hydrolysis time was observed. These phenomena were caused by the degradation of the crystalline structure of cellulose and the formation of the ester sulfate group. The measurement of CNC diameter size was carried out by using the scanning electron microscopy (SEM) technique. The CNC diameter was below 100 nm which indicated the nanoparticle formation was observed at CNC produced at hydrolysis times of 75 and 90 minutes. In conclusion, CNC production was successfully produced from peroxide bleached SPF which is more environmentally friendly than the conventional method using chlorite bleached cellulose. Furthermore, it is needed to optimize the production of SPF CNC in further research.